Efficacy of feeding a diet containing a high concentration of mixed fiber sources for management of acute large bowel diarrhea in dogs in shelters. (17th February 2022) - Lappin, Michael R.; Zug, Amy; Hovenga, Claire; Gagne, Jason; Cross, Emily
Abstract: Background: Use of diets with increased concentrations of dietary fiber is thought to be beneficial in the management of dogs with large bowel diarrhea. Objective: To determine whether feeding a diet with high concentrations of soluble and insoluble fiber to dogs with acute colitis would be superior to feeding a diet with typical fiber levels. Animals: A total of 52 dogs with acute signs of large bowel diarrhea housed in an animal shelter were entered into the study; 11 dogs per diet completed the protocol. Methods: In this randomized, prospective study, dogs with a fecal score of 4, 5, 6, or 7 and signs of acute colitis were fed a high fiber diet (4.54% soluble; 15.16% insoluble fiber) or a standard diet (0.6% soluble; 5.33% insoluble fiber) and fecal scores compared over the course of the study with significance defined as P  < .05. Results: All dogs fed the high fiber diet (11/11; 100%) had a fecal score <5 on the day of adoption or day 9, which was statistically different ( P  < .04) than dogs fed the standard diet (6/11 dogs; 55%; 95% CI: 23‐83). The proportions of stools with a fecal score >4 were greater ( P  = .0001) in the dogs fed the standard diet (29/48 samples; 60%; 95% CI: 45‐74) compared to the high fiber diet (8/50 samples; 16%; 95% CI: 7‐29). Conclusions and Clinical Importance: The results support feeding the high fiber diet described herein to dogs with acute large bowel diarrhea.